Effects of education via Health Belief Model on knowledge and attitude of voluntary health workers regarding Pap smear in urban centers of Qazvin - Yakhforushha, A; Solhi, M; Ebadi Fard Azar, F (Advances in Nursing & Midwifery, 2009)
Background Cervical cancer is the second common cancer after breast cancer in the world. It accounts for 18% of total deaths among women. Purpose This quasi-experimental before-after study was conducted to determine the effects of education based on Health Belief Model (HBM) on knowledge and attitude of voluntary health workers regarding Pap smear in urban centers of Qazvin. Methods 120 health workers took part in the study. A questionnaire completed by the subjects was used for data collection. Different statistical tests including Qui-square, ANOVA, coefficient of correlation etc. were used for data analysis. Results Mean scores of knowledge and elements of HBM (perceived sensitivity, benefits, barriers and severity) about Pap smear test in the subjects before and after intervention and within the elements showed a significant correlation. No significant relationship was found between the elements and such variables as the age and number of children of the workers. A significant relationship was found between the elements (perceived sensitivity and benefits) and educational level of the subjects before the intervention and also (perceived sensitivity and barriers) after that. Conclusion Instructing prevention based on HBM can increase knowledge and make attitude positive in voluntary health workers. Keywords: Health Belief Model (HBM), Knowledge, Attitude, Pap smear.